Ilmu Pendidikan Nasional dan Sistem Kebudayaan: Sebuah Tinjauan Systematic Literature Review - Dwi Adnan Gifari; M. Ilham Desta; Regi Wijaya Kusuma (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
The relationship between national educational science and cultural systems is a central theme in the study of educational philosophy in Indonesia. National education functions not only as a means of knowledge transfer but also as a process of acculturation that instills national values, norms, and identity. This article aims to systematically analyze research findings and theoretical studies related to national educational science and cultural systems through a Systematic Literature Review (SLR) approach. The methods used include identification, selection, and analysis of relevant literature sourced from classic textbooks, national education regulations, and national and international scientific journal articles. The results of the study indicate that national education and culture have a dialectical relationship: culture forms the basis of educational values, while education plays a role in cultural preservation and transformation. These findings emphasize the importance of integrating national cultural values ​​into the curriculum, learning methods, and educational practices, including in the context of physical education and sports.